Electron–ion–neutral temperatures and their ratio comparisons over low latitude ionosphere - Bardhan, Ananna; Sharma, D.K.; Khurana, M.S.; Aggarwal, Malini; Kumar, S. (My University, 2015)
Annual variations in temperatures of plasma (electron–Te, ion–Ti) using SROSS-C2 satellite and neutral (Tn) using NRLMSIS-00 (neutral atmospheric model); have been investigated and their ratios have been compared over half solar cycle (year 1995–2000, F10.7 72–190). The region under consideration spans over 5–35 N geog. latitude and 65–95 E geog. longitude in the Indian sector, at an average altitude of 500 km. Te and Ti exhibit similar, while Tn show completely different diurnal features. During nighttime Te, Ti and Tn attain equilibrium with each other, but plasma cools faster than neutrals. Magnitude of Te and Ti reduces, while that of Tn increases with increasing solar activity. Ratio comparisons (Te/Tn, Ti/Tn and Te/Ti) show higher sensitivity of electrons compared to ions and neutrals. Te/Tn, Ti/Tn exhibits linear/direct relationship with solar flux, while Te/Ti doesn’t. The deviation of Te, Ti and Tn from equilibrium temperature decreases with increasing solar activity.
Keywords: Plasma temperatures (Te and Ti); Neutral temperature (Tn); Ionospheric temperature ratios (Te/Tn, Ti/Tn and Te/Ti); SROSS-C2 satellite; Neutral atmospheric model – NRLMSIS-00; Low latitude F2 region